Characterising electron beam welded dissimilar metal joints to study residual stress relaxation from specimen extraction. (March 2016) - Abburi Venkata, K.; Truman, C.E.; Smith, D.J.; Bhaduri, A.K.
Abstract: Nuclear power plants require dissimilar metal weld joints to connect the primary steam generator made from ferritic steel to the intermediate heat exchanger made from austenitic steel. Such joints are complex because of the mismatch in the thermal and the mechanical properties of the materials used in the joint. Electron Beam (EB) welding is emerging as a promising technique to manufacture dissimilar joints providing a great many advantages over conventional welding techniques, in terms of low heat input, high heat intensity, narrow fusion and heat affected zones, deeper penetration and increased welding speeds. However before this method can be considered for implementation in an actual plant, it is essential for a careful and a comprehensive outlining of the joint characteristics and the apparent effects on performance during service. In the present study, an EB welded joint was manufactured using austenitic AISI 316LN stainless steel and a ferritic-martensitic P91 steel, without the addition of filler material. Neutron diffraction measurement was conducted on the welded plate to measure the residual stress distribution across the weld as well as through the thickness of the plate. A finite element analysis was conducted on a two-dimensional cross-sectional model using ABAQUS code to simulate the welding process and predict the residual stresses, implementing the effects of solid-state phase transformation experienced by P91 steel. The predicted residual stresses were transferred to a 3D finite element model of the plate to simulate the machining and extraction of a C(T) blank specimen from the welded plate and the extent of stress relaxation is studied.